Representation of Trigonometry Graph Funcsion Colage Students Using GeoGebra - Mohammad Archi Maulyda; Erry Hidayanto; Swasono Rahardjo (International Journal of Trends in Mathematics Education Research, 2019)
This descriptive qualitive research aims to describe the forms of mathematics representation that appear among college students whom try to understand the relation between the change of trigonometry function coefficient and its graph through GeoGebra media. A class consists of 30 college students choosen as research subjects and they are given worksheets. From their work, it can be seen that there are 3 types of tendency of representation forms which is used by college students to solve their worksheet. From each type of tendency, a worksheet of student is choosen randomly for further investigation since it can represent others’ work. The research result shows that college students represent GeoGebra view in 3 forms. They are verbal representation, mathematics expression representation, and visual representation.